Is Prick of Conscience Associated With the Sensation of Physical Prick? - Ku, Xyle; Lee, Jonghwan; Lee, Hyunyup (Frontiers in Psychology, 2020)
“Prick of conscience” is a phrase to express feelings of guilt in both English and Korean. Particularly in South Korea, guilt is metaphorically associated with a sense of touch by pricking. Koreans commonly express feelings of guilt by using the metaphor, “It pricks my conscience”. Across three studies, we examined whether prick of conscience (i.e., feelings of guilt) is grounded in bodily experiences of physical prick (e.g., a needle prick), using a sample of Koreans. Participants who recalled past unethical acts were less likely to choose a needle prick rather than medication as a treatment for indigestion, whereas those who recalled ethical acts presented no significant difference in their willingness to receive either treatment (Study 1). Participants who decided to lie sensed the finger prick deeper and felt more pain as compared to those in the truth group or the control group (Study 2). Lastly, participants who had the finger prick rendered harsher moral judgments than participants in the control condition (Study 3). In line with an embodied cognition framework, these findings suggest that prick of conscience is not just a linguistic metaphor but can be embodied as physical sensations in forms of pricking.